(untitled) (Al-Farooq Journal of Sciences, 2025)
The comparative study between Classical Arabic and the colloquial Libyan dialect, which I conducted on the phenomenon of substitution by tracing its occurrences in both linguistic varieties through a descriptive, analytical, and comparative approach, showed that the Libyan dialect agrees with Classical Arabic in the cause of substitution, which lies in the pursuit of ease, smooth phonetic flow, and economy of effort. It also showed that the Libyan dialect is deeply rooted in its phonetic structure and generally preserves the phonological rules and principles of Arabic without deviating from them. It moves between morphological analogy and transmitted Arabic usage, without always adhering strictly to either the inherited analogical or transmitted patterns. What was analogical in Classical Arabic may appear as transmitted usage in the Libyan dialect, while what was transmitted usage may sometimes become analogical and regular, due to the stability of such usage in Libyan speech.